3t+3=5t-2

Simple and best practice solution for 3t+3=5t-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3t+3=5t-2 equation:


Simplifying
3t + 3 = 5t + -2

Reorder the terms:
3 + 3t = 5t + -2

Reorder the terms:
3 + 3t = -2 + 5t

Solving
3 + 3t = -2 + 5t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-5t' to each side of the equation.
3 + 3t + -5t = -2 + 5t + -5t

Combine like terms: 3t + -5t = -2t
3 + -2t = -2 + 5t + -5t

Combine like terms: 5t + -5t = 0
3 + -2t = -2 + 0
3 + -2t = -2

Add '-3' to each side of the equation.
3 + -3 + -2t = -2 + -3

Combine like terms: 3 + -3 = 0
0 + -2t = -2 + -3
-2t = -2 + -3

Combine like terms: -2 + -3 = -5
-2t = -5

Divide each side by '-2'.
t = 2.5

Simplifying
t = 2.5

See similar equations:

| 7(5f-8)=f+7 | | -1.3j+0.40=-1.16 | | 40x+26y=486.70 | | n^2-63=0 | | 40x+31y=332.45 | | 5w-10=90 | | b^6+8g^6= | | 4x+53+5x=8 | | 9y+3+2y+6=15y-11 | | x(x-2)(x+14)(x-5)=0 | | Z^2+8z-1=0 | | 36x^4-36= | | 2c+4=-9+5 | | (x^2+2x)(x-3)=0 | | 5(16p)p= | | lgx-lgy=1 | | lgx-lgy=1 | | -4x^2+808x-9120=0 | | 4x+1+12=2 | | 35-16(c-1)=c | | X-4-2=10 | | -(w+x)+2(2x+w)= | | 5(3x-7)-2(x+3)-18x= | | y+(-13)=31 | | 5.5x+x=377 | | 3(2n-3)=21 | | 8(8y-1)=y+7 | | 6x+10-3x=9+2x+5 | | -16+26=-2(x+8) | | 6+m=12 | | 0.50x+0.50(10)=0.25(98) | | 2(f-6)=2 |

Equations solver categories